2015
DOI: 10.1111/bjop.12134
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent reading skill and engagement with digital and traditional literacies as predictors of reading comprehension

Abstract: The present study investigates the concurrent predictors of adolescent reading comprehension (literal, inferential) for fiction and non-fiction texts. Predictors were examined from the cognitive (word identification, reading fluency), psychological (gender) and ecological (print exposure) domains. Print exposure to traditional and digital texts was surveyed using a diary method of reading habits. A cross-sectional sample of 312 students in early (11-13 years) or middle adolescence (14-15 years) participated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 95 publications
(77 reference statements)
2
36
1
7
Order By: Relevance
“…Future research should therefore focus upon understanding the link between different reading activities and the different components of reading developed by different types of text. Similarly, future research might also investigate whether other skills are developed when young people engage in reading other text types (in a spirit similar to the work of Coiro & Dobler, 2007) and the differences between digital and traditional forms of Link between fiction and reading skills 197 reading material (as per Duncan et al, 2015). Finally, the focus within this article has been 15-year-olds within developed (OECD) countries only.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should therefore focus upon understanding the link between different reading activities and the different components of reading developed by different types of text. Similarly, future research might also investigate whether other skills are developed when young people engage in reading other text types (in a spirit similar to the work of Coiro & Dobler, 2007) and the differences between digital and traditional forms of Link between fiction and reading skills 197 reading material (as per Duncan et al, 2015). Finally, the focus within this article has been 15-year-olds within developed (OECD) countries only.…”
Section: Discussionmentioning
confidence: 99%
“…Another study which looks at students' exposure to both printed and digital texts also found that gender and ecological factor such as print exposure are important determinants in reading comprehension skills development among adolescent readers from various socio-economic status (SES) backgrounds [3]. Female students were found to read more than the male students though this reading frequency does not necessarily reflect satisfactory reading skills mastery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…La discusión sobre el futuro de la lectura ya no se centra en la desaparición del libro, entrando en escena otros temas como los nuevos soportes y los nuevos hábitos de lectura motivados por el crecimiento del uso de dispositivos digitales (Duncan, McGeown, Griffiths, Stothard, & Dobai, 2016;Pinto, Pouliot, & Antonio Cordón-García, 2014;Shimray, Keerti, & Ramaiah, 2015;Wang, Chiu, Ho, & Lo, 2016). Así, como primera conclusión se puede afirmar que los hábitos de lectura sufren cambios considerables cuando se hacen desde soportes electrónicos.…”
Section: Fomento De La Lectura Digital: Formar Y Animar Los Lectores unclassified